Effects of lysophosphatidic acid receptor 5 on NLRC4 inflammasome in brain tissues of transient cerebral ischemia/reperfusion rat. (1st March 2022) - Zhang, Xuling; Huang, Tao; Lang, Lubo; Yu, Ling
Aim: To explore whether LPA5 was involved in the inflammatory responses in CI/R injury by regulation of NLRC4. Method: The cerebral I/R model in rats was constructed with ischemia of 2h and different time points of reperfusion. After that, western blot was used to determine protein expression (LPA5, NLRC4, AIM2, caspase-1, cleaved-caspase-1, mature IL-1β, and precursor IL-1β). And LPA5 and NLRC4 expression were also detected by using immunofluorescence experiment. Afterward, two sequence of LPA5-siRNA were injected into rats via intracerebroventricular administration. TTC staining and HE staining were performed. Result: As the reperfusion time was prolonged, LPA5 content was continuously increased, and the highest expression of NLRC4 was found at 4h of reperfusion. And protein expression of AIM2, cleaved-caspase-1, and mature IL-1β was also at highest level at 4h. And after reperfusion of 4h, LPA5 siRNA1# or 2# was injected into lateral ventricles. LPA5 silence markedly reduced the infract volume and improved the histological change of ischemic zone. And LPA5 silence significantly downregulated NLRC4, AIM2, and the ratio of cleaved-caspase-1/caspase-1 and mature IL-1β/precursor IL-1β. And compared with LPA5-siRNA2#, LPA5-siRNA1# exerted a more significant effect. Conclusion: Low expression of LPA5 can protect against the inflammatory responses in CI/R model of rats through inhibiting NLRC4 inflammasomes.